Manifestation of Multiple Oral Ulcerations and Facial Palsy in Patient with History of Typhoid Fever - Nasrul, Adenia A.; Putri, Anggun Mauliana; Usman, Nur Asmi; Yusran, Ali; Israyani, Israyani; Indirayani, Indirayani (Journal of Case Reports in Dental Medicine, 2025)
Objective: Typhoid fever is infectious disease caused by Salmonella typhi. Patients with typhoid fever might have several clinical manifestations, in addition, post-infection, patients are still at risk of experiencing posttreatment complications. The aim of this article is to report a case of multiple oral ulcerations in a post-typhoid fever patient to improve the knowledge and awareness of dentists in handling ulcer lesions cases in the oral mucosa, especially in patients with history of infectious diseases. Methods: An-54-year-old female came with the chief complaint of multiple painful ulcers on the oral mucosa since 3 days ago after following hospitalization for typhoid fever for 8 days. The patient typically experiences only 2 ulcers and healed without medication. Extral oral examination revealed the facial asymmetry on sinistra. The patient was prescribed dexame dexamethasone gargle and referred to neurologist. The hematology examination revealed the decreased hemoglobin and erythrocyte levels. The patient has also been diagnosed with Bell’s Palsy and treated with methylprednisolone. Therefore, the working diagnosis is Aphthous-like ulcers related to typhoid fever Result: Oral ulcers can occur in typhoid patients due to anemic condition that triggers malnutrition deficiency of vitamin B12, folic acid, and iron which causing damage to the oral mucosa, playing a role in triggering and worsening oral ulcers. Anemia in typhoid is caused by decrease of erythrocyte production in bone marrow due to infection leading to anemia. Conclusion: Multiple oral ulcers can be triggered by systemic condition, such as typhoid fever.